Character Education, Learning Models, Blended Learning: (KAJIAN KONSEPTUAL) - Tuti Marlina (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
The pandemic has forced educators to adapt to new habits in carrying out the learning process. Learning that was originally only face-to-face has turned into online. This is what then raises various problems so it is necessary to applyblended learning. In order for education to be in accordance with its objectives, in the learning process it is necessary to instill character education. The purpose of this study is to build a concept of character education based on a blended learning model. The research method used is a qualitative study of literature with conceptual results. The results of this study indicate that the implementation of character education based on the blended learning is carried out by modifying the learning tools (syllabus and lesson plans) to be character-based. As for the implementation of learning, teachers need to implement various teaching techniques, methods and learning media based on character and implemented in combination (online-offline). The teaching techniques in question are Live Events (Face-to-Face Learning), Self-Paced Learning (Independent Learning), Collaboration (Collaboration), Assessment (Assessment or Measurement of Learning Outcomes), Performance Support Materials (Support Learning Materials), Filtering Important Information from Internet. While the learning method consists of: Live In, Exemplary, Student Activity (Inquiry Learning), Joint Search (Information Search), Discovery (Discovery Learning). As well as learning media consisting of software (Web, Streaming Video, Audio and Social Media) and hardware (CD, Smartphone, Computer, Laptop, LCD, Practicum Equipment, etc.).